Evaluation of Mobile Application Service on User Loyalty Using Expectation Confirmation Model - Muhammad Qomarul Huda; Muhammad Shidqa Irahman; Nur Aeni Hidayah; Nida’ul Hasanati; Yuni Sugiarti (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2026)
Background: Mobile-based Academic Information Systems (AIS) have become essential for improving accessibility and efficiency in higher education. UIN Jakarta’s AIS Mobile aims to support academic activities; however, user loyalty remains low, as many students prefer accessing services via the web platform. Objective: This study evaluates AIS Mobile services and identifies key factors influencing user loyalty using an extended Expectation Confirmation Model (ECM). Methods: A quantitative approach was employed, involving 334 respondents selected through purposive sampling. Data were collected via an online questionnaire and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0.9.3. The proposed model integrates ECM constructs—confirmation, perceived usefulness, satisfaction, and continuance intention—with additional variables: system quality, information quality, trust, habit, and loyalty. Results: Findings indicate that eight hypotheses were supported, confirming significant relationships among confirmation, perceived usefulness, trust, habit, and continuance intention in shaping loyalty. Satisfaction, however, showed no significant effect on continuance intention. The model demonstrates strong explanatory power, with R² values of 0.737 for continuance intention and 0.726 for satisfaction. Habit exhibited the largest effect size, emphasizing its role in sustaining usage. Implications: To enhance user loyalty, developers should prioritize improving system reliability, security, and usability while fostering habitual engagement through intuitive design and personalized features. These insights provide actionable strategies for strengthening AIS Mobile adoption in Islamic higher education contexts.